Proyecto de inversión para el establecimiento de un café gourmet en la ciudad de Guayaquil - Yoong Parraga, Cristina Edith (2009)
The objective of this project is to analyze the restaurant and cake shops’ market, and to calculate the revenue of a coffee shop with special characteristics that make it different from the usually known in Guayaquil. The idea is to set up a coffe shop with an elegant style that includes music, kind waiters, gourmet menu and special decorations of the dishes. A place where the menu includes home made ice cream and milkshakes with non-typical flavors, variety of deserts, snacks, sandwiches, hot and cold beverages. In addition, the “café” will offer cakes and deserts, cupcakes and cookies packed in boxes with charming decoration; all made at home. To run with this project, it was necessary to do a market investigation that allows know the consumer preferences, and what to offer them. It was also necessary to assign the cost properly, considering the type of the business, and the financial analysis to determine its revenues.